The importance of rapport in the process of learning (Journal of Pedagogical Inventions and Practices, 2023)
Rapport is a harmonious relationship between people who established mutual trust. Besides, the rapport plays a crucial role in learning process and it is espoused as the way to help teachers reach moving goals by creating learners who can function powerfully within complex societies